Impact of obesity in the adult woman’s reproductive health - Manrique, Helard (2018)
Obesity is a multifactorial epidemic that involves genetic, environmental and social factors. We will review the effect of obesity on female reproduction. Adipose tissue is involved in the production of various hormones related to metabolism, the homeostasis of the individual and also in reproduction in both women and men. We will review the various changes produced by overweight and obesity in women and the hormonal changes that influence women’s reproductive health.